2019
DOI: 10.1177/1756286419837809
|View full text |Cite
|
Sign up to set email alerts
|

Post-natalizumab disease reactivation in multiple sclerosis: systematic review and meta-analysis

Abstract: Background: Natalizumab (NTZ) is sometimes discontinued in patients with multiple sclerosis, mainly due to concerns about the risk of progressive multifocal leukoencephalopathy. However, NTZ interruption may result in recrudescence of disease activity. Objective: The objective of this study was to summarize the available evidence about NTZ discontinuation and to identify which patients will experience post-NTZ disease reactivation through meta-analysis of existing literature data. Methods: PubMed was searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 67 publications
(421 reference statements)
9
67
1
5
Order By: Relevance
“…Controversial findings have been reported about the association between the number of NTZ infusions and the risk for reactivation, as some studies have reported higher reactivation rates in patients with shorter exposure to NTZ (Lo Re et al, 2015;Miravalle et al, 2011;Prosperini et al, 2019;Vellinga et al, 2008). In our analysis, we did not detect any correlation between the number of NTZ infusions and the risk for reactivation.…”
Section: Multivariate Analysiscontrasting
confidence: 77%
See 1 more Smart Citation
“…Controversial findings have been reported about the association between the number of NTZ infusions and the risk for reactivation, as some studies have reported higher reactivation rates in patients with shorter exposure to NTZ (Lo Re et al, 2015;Miravalle et al, 2011;Prosperini et al, 2019;Vellinga et al, 2008). In our analysis, we did not detect any correlation between the number of NTZ infusions and the risk for reactivation.…”
Section: Multivariate Analysiscontrasting
confidence: 77%
“…As expected, reactivation of MS has been shown to occur during the first year after discontinuation of NTZ in some patients (Fox et al, 2014;Gueguen et al, 2014;Havla et al, 2011;Iaffaldano et al, 2015;Kerbrat et al, 2011;Lo Re et al, 2015;O'Connor et al, 2011;Salhofer-Polanyi et al, 2014;West and Cree, 2010). A recent systematic review and meta-analysis of six studies demonstrated that younger age, higher number of relapses, and gadolinium-enhancing lesions before initiation of treatment as well as fewer NTZ infusions were associated with an increased risk for disease reactivation after cessation of treatment (Prosperini et al, 2019).…”
Section: Introductionmentioning
confidence: 57%
“…Most, but not all, international and national recommendations suggest that natalizumab therapy should not increase the risk of severe COVID-19 ( Question 11). Indeed, cessation or interruption of natalizumab treatment carries a considerable risk of MS disease exacerbation or rebound activity in patients with highly active MS 66 , the consequences of which are likely to outweigh the risk of COVID-19. Natalizumab has been suggested as a bridging therapy (a drug that can be used for an immediate effect owing to its fast onset of activity and high efficacy but that is not necessarily considered a long-term option) during the COVID-19 pandemic, and the first reports of SARS-CoV-2 infection in patients receiving natalizumab therapy have suggested no increase in risk 67,68 .…”
Section: Natalizumabmentioning
confidence: 99%
“…The risk of disease reactivation after natalizumab discontinuation may be mitigated somewhat if treatment is switched during a period of relative disease quiescence or if the transition time is < 1-2 months. 145,146 There are limited data that switching from natalizumab to alemtuzumab is more effective than to fingolimod. 147 However, switching from natalizumab to any DMT with a long duration of action may be considered a high-risk approach since treatment could not be withdrawn in such circumstances if the patient had subclinical PML.…”
Section: Treatment Sequencingmentioning
confidence: 99%